Task-based learning for enhanced mastery of language. - Wee, Vivien Mui Eik *; Jong, Emmy Ee Mei (2013)
Teachers’ observations suggest that task-based learning (TBL) enhances the four language skills at a faster rate and makes teaching and learning more interactive, enjoyable and effective. The objective of this paper is to examine how TBL accelerates improvement because it requires greater involvement of the students in the learning process and students tend to feel a stronger sense of ownership as they are encouraged to take the lead in figuring out the best way to achieve the specific goals of the tasks. TBL makes it possible for students to take responsibility for a major part of the work, while enabling the lecturer to focus on providing relevant explanation and feedback. This paper describes these aspects, drawing on the prior experience of students using task-supported language activities (TSLA) in their secondary school years. The subjects of this paper are students in the Australian Matriculation (AUSMAT) Programme from January and April 2013 intakes who have taken English as an Additional Language or Dialect (EALD) as a core subject. Their reflective essays provided relevant data as the basis of this research. The responses indicate that noticeable improvement in the students’ oral and written skills resulted from the TBL approach.